PENGARUH UKURAN PERUSAHAAN, KONDISI KEUANGAN, PERTUMBUHAN PERUSAHAAN, UKURAN KAP, OPINI AUDIT TAHUN SEBELUMNYA, DAN LEVERAGE TERHADAP PEMBERIAN OPINI GOING CONCERN (Studi pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia) - Listari, Alya; Andreas, Andreas; Ilham, Elfi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2018)
The purpose of this research was to test and analyze the effect between company size, financial condition, company growth, KAP size, prior year audit opinion, and leverage on granting going concern opinion. The population in this study is all manufacturing companies listed in Indonesia Stock Exchange at 2011- 2015. Sampling was done by purposive sampling method. Based on purposive sampling method, sampling obtained by 155 companies. The data was analysed by using logistic regression analysis with SPSS version 25.0. Based on the result of test, indicate that company size, company growth, and prior year audit opinion have an effect on granting going concern opinion. While financial condition, KAP size and leverage does not have an effect on granting going concern opinion.Keyword : Company Size, Financial Condition, Company Growth, KAP Size, Prior Year Audit Opinion, Leverage, and Going Concern Opinion.